1930. Damage detection of concrete piles subject to typical damages using piezoceramic based passive sensing approach - Feng, Qian; Xiao, Han; Kong, Qingzhao; Liang, Yabin; Song, Gangbing (Journal of Vibroengineering, 2016)
Pile foundations are typically comprised in concealed construction work. In recent years, some major categories of concrete piles subject to typical damages have caused a lot of engineering disasters and accidents. These accidents have been caused by collapse of civil structures resulting in great casualties and economic loss. Therefore, damage detection and real-time health monitoring on foundation piles is an urgent research requirement. In this research, a piezoceramic based passive sensing approach is proposed to detect typical damages types of concrete piles, including partial mud intrusion, secondary concrete pouring interface, circumferential crack, and full mud intrusion. In this passive sensing approach, induced stress waves are generated by the impact hammer on the top surface of a pile and one smart aggregate embedded on the bottom of each pile is used as a sensor to receive the propagating wave signals. These sensors are embedded before pouring concrete. Structural defects affect the natural frequency of the pile. The power spectrum of piles with different types of damage were compared by plotting the sensor signals in frequency domain. The natural frequency decreases with the increase in defect severity. The experimental results demonstrate that the proposed approach can detect all four typical damage types in concrete piles.